A Deeper Understanding of Reuse: Learning Designs, Activities, Resources and their Contexts. Issue 1 (10th February 2016) - Wills, Sandra; Pegler, Chris
This paper positions discussion of learning designs in the broad context of reuse and repurpose. It proposes that not enough attention has been given to the purpose of reuse and the motivation of those who choose to share or use reusable learning resources. There is a need for both a broad and deep understanding of what occurs when designs, activities and resources with potential for reuse are encountered in practice. The paper compares two longitudinal case-based studies, one from Australia and one from the UK. The independently conceived and executed investigations shed light on what influences reuse of designs, activities, and resources. While Wills has tracked the reuse of online role play designs, activities and resources to create a deep understanding of reuse and repurposing of specific resources, Pegler has drawn on five significant UK-based case studies representing different levels of reuse-focused activity, ranging from personal to national initiatives. Mapping the two studies, both representing extensive doctoral research (Wills, 2010 andPegler, 2011 ), reveals a general consistency in the factor types identified and a common focus on the influence, complexity and importance of context. In exploring academics' thresholds for reuse, Pegler proposes the concept of "zones of proximity" and Wills proposes "nuances of reuse". Both concepts highlight that reuse currently more typically occurs in close contexts. The paper points to the need for research to be directed towards understanding how to better facilitate the goal of sharing and reusing of learning designs, resources and activities, globally.